A peculiar new virus-spermatozoon association in the bug Raphigaster nebulosa (Poda) (Heteroptera-Insecta). Issue 1 (January 2016) - Mercati, David; Dallai, Romano
Abstract: The sperm of the heteropteran bug Raphigaster nebulosa (Poda) are of two types, differing in length and size of their flagella. The thicker sperm are shorter than the thinner ones and have large mitochondrial derivatives. The presence of virus particles associated with the plasma membrane of thinner sperm is described for the first time; thicker sperm are immune to virus infection. The fact that virus particles are present on thinner sperm only initiates considerations on the transmission of virus. Highlights: The heteropteran bug Raphigaster nebulosa has sperm of two types, differing in length and size. Greater sperm are shorter than thinner ones and have large mitochondrial derivatives. Thinner sperm only have their plasma membrane associated with virus particles. The viruses are bullet-shaped suggesting the occurrence of a rhabdovirus species.